Nano Crystal Cellulose Incorporated Poly Vinyl Alcohol (PVA) Hydrogel for Industrial Waste Water Treatment - Zianor Azrina, Z. A.; Beg, M. D. H.; R. M., Yunus; Ridzuan, Ramli (AENSI Publishing, 2017)
In this work, nanocrystalline cellulose (NCC) was extracted from raw oil palm empty fruit bunch (EFB) fiber. The NCC microstructure was evaluated by X-ray diffraction (XRD) analysis. Scanning electron microscope reveals the comparative surface morphology of raw EFB and NCC. The freeze-thawing cyclic process was applied to fabricate NCC incorporated polyvinyl alcohol (PVA) (NCC-PVA) hydrogel . The aim of this work is to improve removal capacity of methylene blue (MB) dye from industrial waste water using NCC incorporated PVA hydrogel. The gel fraction NCC-PVA hydrogel is lower as compared to neat PVA hydrogel. The NCC-PVA hydrogel was applied to remove the methylene blue (MB) dye from industrial waste water. The NCC enhanced the dye absorption capacity of NCC-PVA hydrogel as compared to neat PVA hydrogel.